Use of Maternal Health Services by Remote Dwelling Aboriginal Women in Northern Australia and Their Disease Burden. Issue 3 (18th September 2013) - Bar‐Zeev, Sarah; Barclay, Lesley; Kruske, Sue; Bar‐Zeev, Naor; Gao, Yu; Kildea, Sue
Abstract Background Disparities exist in pregnancy and birth outcomes between Australian Aboriginal women and their non‐Aboriginal counterparts. Understanding patterns of health service use by Aboriginal women is critical. This study describes the use of maternal health services by remote dwelling Aboriginal women in northern Australia during pregnancy, birth and the postpartum period and their burden of disease. Methods A retrospective cohort study of maternity care for all 412 maternity cases from two remote Aboriginal communities in the Northern Territory of Australia, 2004–2006. Primary endpoints were the number and type of maternal health‐related complications and service episodes at the health centers and regional hospital during pregnancy, birth, and the first 6 months postpartum. Results Ninety‐three percent of women attended antenatal care. This often commenced late in pregnancy. High levels of complications were identified and 23 percent of all women required antenatal hospitalization. Birth occurred within the regional hospital for 90 percent of women. By 6 months postpartum, 45 percent of women had documented postnatal morbidities and 8 percent required hospital admission. The majority of women accessed remote health services at least once; however, only one third had a record of a postnatal care within 2 months of giving birth. Conclusion Maternal health outcomes were poor despite frequent service use throughout pregnancy, birth, and the first 6 months postpartum suggesting quality of care rather than access issues. These findings reflect outcomes that are more aligned with the developing rather than developed world and have significant implications for future planning of maternity services that must be urgently addressed.